Single Stage in Situ Suture Repair of a Multi-Ligament Knee Injury, an Observational Study - Hussain Bux Palh, Rakan Ali Salem Yamani, Masood Ahmed Qureshi, Saeed Ullah, Ali Muhammad Bhutto, Abdul Rehman Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: This study aims to observe the clinical outcomes associated with in situ single-stage suture repair for knee dislocation in patients suffering from multiple knee ligament injuries with the use of unabsorbable materials of the suture. Study design: A retrospective observational study Place and Duration this study was conducted in Gambat Medical College Pir Syed Abdul Qadir Shah Jellani Institute of Medical Science GIMS Gambat from May 2021 to May 2022. Methodology: In this study35 patients treated surgically with in situ suture repair were recruited. A retrospective analysis was done on 35 patients with a mean follow-up score of 3.8 ± 1.3 years. Patients were undergone in situ surgical procedures for all the ruptured ligaments followed by a proper rehabilitation protocol post-operatively. Outcome variables were assessed by Lysholm score, satisfactory score, Meyers functional rating score, VAS score, and Tegner score. Results: Results of the study states that the mean follow-up a score of VAS was recorded as 1.98 ± 0.4, Lysholm score was recorded as 82.5 ± 6.7, and the patient satisfaction score was recorded as 7.5 ± 0.9. Statistically, significant differences have been observed between the pre and post-scores of ranges of motion and Tegner activity scores with a p-value of < 0.001 for both activity and ROM scores. Final follow-up of these patients reported that patients were left with no ligament laxity except for two patients who were unable to restore back to work. Among 35 patients, 5 were unable to achieve full ROM and had stiffness whereas two had infections at the surgical site. Conclusion: In situ suture repair of multiple ligaments had shown significant improvement in terms of ligament repair and early rehabilitation and therefore can be considered an effective treatment approach for the management of multiple ligament injuries. Keywords: Multiple ligament injuries, in situ repair, knee dislocation, cruciate ligament injury, single-stage repair.